ASSESSMENT OF INCIDENCE OF FUNGAL BLOODSTREAM INFECTIONS IN LATE-ONSET SEPSIS AMONG VLBW BABIES IN A TERTIARY CARE CENTRE (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Late-onset sepsis is a major cause of morbidity and mortality in very low birth weight (VLBW) neonates, with fungal infections, particularly Candida species, emerging as an important etiological agent. The incidence and outcome of neonatal candidemia vary across neonatal intensive care units, especially in high-risk VLBW infants. Methodology: This prospective observational study was conducted in the Department of Paediatrics, Sree Mookambika Institute of Medical Sciences, Kulasekharam, from March 2025 to February 2026. VLBW neonates (1.0–1.5 kg) with late-onset sepsis were included, while those with early-onset sepsis and birth weight 1.5 kg were excluded. Clinical features, laboratory data, and culture reports were analyzed to identify fungal sepsis. Statistical analysis was performed using Chi-square test and Fisher’s exact test, with p